CONTEXTUAL CLIL INTEGRATION TO ENHANCE ACADEMIC SPEAKING SKILLS IN HIGHER EDUCATION - Kakhkhorova Nigina Abdivakhidovna (American Journals Publishing, 2025)
This article investigates into the way non-linguistic university students might enhance their speaking skills by combining contextual instruction with Content and Language Integrated Learning (CLIL). The paper focuses on activation tactics, guided understanding, concentrated speaking activities, and mixed-level group interactions, drawing on previous classroom experiences such as environmental English courses and contextual practice. It offers a framework for improving speaking fluency, confidence, and material understanding through contextualized exercises such as pair presentations, reverse outlining, and problem-solving talks. There are methodological implications and practical recommendations for teaching foreign languages in non-linguistic fields.
Keywords: Speaking skills development, communicative competence, content-based instruction, task-based speaking activities, integrated skills approach, essential pedagogical components